2007
DOI: 10.1111/j.1467-9280.2007.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control Under Stress

Abstract: ABSTRACT-This study investigated the effect of stress on cognitive control in task shifting. Subjects shifted between two tasks in an explicit cuing paradigm. Shift costs (i.e., performance decrements on task shifts relative to task repetitions) were measured for a long and a short cuestimulus interval (CSI). Stress was varied by administering low-stress and high-stress IQ scales to two groups of subjects. In the low-stress group, shift costs were reduced with an increased CSI, a result that typically indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 29 publications
2
22
1
Order By: Relevance
“…If so, even worriers and those with GAD who have high trait-level capacity for effortful control may experience increasing autonomic arousal symptoms during prolonged periods of worry, as their ability to suppress images and shift to a verbal mode of processing wanes. Second, during periods of other cognitive load or stress, such individuals may experience heightened autonomic arousal symptoms during bouts of worry because their capacity for effortful control and ability to constrain worry to a verbal mode has been depleted (Steinhauser et al, 2007). Furthermore, such heightened arousal may lead to an upward spiral in worry and autonomic arousal symptoms because perceptions of arousal appear to maintain worry among those high in GAD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…If so, even worriers and those with GAD who have high trait-level capacity for effortful control may experience increasing autonomic arousal symptoms during prolonged periods of worry, as their ability to suppress images and shift to a verbal mode of processing wanes. Second, during periods of other cognitive load or stress, such individuals may experience heightened autonomic arousal symptoms during bouts of worry because their capacity for effortful control and ability to constrain worry to a verbal mode has been depleted (Steinhauser et al, 2007). Furthermore, such heightened arousal may lead to an upward spiral in worry and autonomic arousal symptoms because perceptions of arousal appear to maintain worry among those high in GAD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence has shown that stress disrupts synaptic plasticity and cognitive control processing in prefrontal cortex (Alexander et al, 2007, Diamond et al, 2007, Steinhauser et al, 2007), although it facilitates striatum-dependent processes (Schwabe et al, 2007, Quirarte et al, 2009). The similarity between cocaine and stress effects on model-free and model-based learning mechanisms is extremely intriguing, especially because stress is a critical risk factor for the development of addiction as well as for relapse to drug seeking after abstinence (Piazza and Le Moal, 1996, Sinha, 2001).…”
Section: Discussionmentioning
confidence: 99%
“… 6 We thank Marco Steinhauser for noting that Steinhauser et al (2007) arrived at a similar conclusion to account for changes in preparation strategies under stress. Specifically, it was argued that switch-specific preparation requires that task switches are detected and this switch detection is resource-consuming.…”
mentioning
confidence: 83%